2018
DOI: 10.1080/10408363.2018.1529734
|View full text |Cite
|
Sign up to set email alerts
|

D-dimer: Preanalytical, analytical, postanalytical variables, and clinical applications

Abstract: D-dimer is a soluble fibrin degradation product deriving from the plasmin-mediated degradation of cross-linked fibrin. D-dimer can hence be considered a biomarker of activation of coagulation and fibrinolysis, and it is routinely used for ruling out venous thromboembolism (VTE). D-dimer is increasingly used to assess the risk of VTE recurrence and to help define the optimal duration of anticoagulation treatment in patients with VTE, for diagnosing disseminated intravascular coagulation, and for screening medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
103
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 240 publications
(559 reference statements)
1
103
0
11
Order By: Relevance
“…Our study also reported the disturbed coagulation status of non‐survivor patients. Disseminated intravascular coagulation (DIC) is a persistent activation of the hemostatic system mainly caused by infection, inflammation, and surgery 16 . A recent study showed that COVID‐19 severe patients have ischemic changes in the fingers and may develop DIC 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study also reported the disturbed coagulation status of non‐survivor patients. Disseminated intravascular coagulation (DIC) is a persistent activation of the hemostatic system mainly caused by infection, inflammation, and surgery 16 . A recent study showed that COVID‐19 severe patients have ischemic changes in the fingers and may develop DIC 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Blood clots are dissolved by plasmin, a protein which degrades fibrin networks, producing fibrin degradation products [33], which include D-dimer [41]. D-dimer is also an important circulating inflammatory biomarker [42][43][44][45][46]. The D-dimer protein contains two cross-linked D fragments from the fibrinogen protein formed upon degradation of the fibrin gel, the core component of blood clots [18].…”
Section: Introductionmentioning
confidence: 99%
“…D-dimer assays are also being used to predict the risk of recurrence of thromboembolic events, to diagnose and monitor disseminated intravascular coagulation, to guide anticoagulant therapy, and as a prognostic factor for thrombotic complications in patients with malignant neoplasms, serious infections, pre-eclampsia, migraine, or placental abruption. 24,25 However, its clinical usefulness is limited by some clinical conditions and individual heterogeneity, which raises the importance of cut-off points adjusted for population groups. 24 Models that combine D-dimer with other biomarkers could improve its diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%